Description of a new species of Katerinaella Vlasak & Santos-Silva from Bolivia (Coleoptera, Cerambycidae, Cerambycinae, Rhinotragini) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2024)
A new species of Katerinaella Vlasak & Santos-Silva, 2018 is described from Bolivia. A key to species of Katerinaella is provided.